1978
DOI: 10.1073/pnas.75.8.3886
|View full text |Cite
|
Sign up to set email alerts
|

Origin and direction of replication in mitochondrial DNA molecules from Drosophila melanogaster.

Abstract: From a consideration of the various structural forms of partially replicated mitochondrial DNA (mtDNA) molecules from Drosophila melanogaster embryos observed in the electron microscope, it appears that the majority of molecules are replicated by a highly asymmetrical mode in which synthesis on one strand is up to 99% complete before synthesis on the second strand is initiated. Replication of the minority of molecules involves a more nearly symmetrical synthesis of the two complementary strands. The D. melanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
4

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 26 publications
5
74
0
4
Order By: Relevance
“…In all species examined, the free 59 ends of the minor coding strands were found in a very narrow range of several nucleotides in the A 1 T-rich region, located at the middle portion for four Drosophila species, T. castaneum, and L. migratoria and near the 12S rRNA gene for B. mori ( Figures 2B, 3B, and 4). D. yakuba and D. virilis were used in a previous mapping study using electron microscopy, and the free 59 ends were found in the middle of the A 1 T-rich region (Goddard and Wolstenholme 1980). Therefore, the results of the present study are consistent with the previous results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In all species examined, the free 59 ends of the minor coding strands were found in a very narrow range of several nucleotides in the A 1 T-rich region, located at the middle portion for four Drosophila species, T. castaneum, and L. migratoria and near the 12S rRNA gene for B. mori ( Figures 2B, 3B, and 4). D. yakuba and D. virilis were used in a previous mapping study using electron microscopy, and the free 59 ends were found in the middle of the A 1 T-rich region (Goddard and Wolstenholme 1980). Therefore, the results of the present study are consistent with the previous results.…”
Section: Discussionsupporting
confidence: 83%
“…If the recognition sequence for replication initiation is included in the repeated sequence, the O R 's must also be situated tandemly in D. melanogaster mtDNA. However, the O N has been found only at the central portion of the A 1 T-rich region by electron microscopy (Goddard and Wolstenholme 1978). The prominent T-stretch in the major coding strand is located at the central intervening portion between the type I and II repeats and is excluded from the repeated sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about the mechanism of mtDNA replication in Drosophila (47), and new experimental approaches have led to a reconsideration of the long standing model proposed for mouse and man (48 -50). In the recent model, mtDNA replication is proposed to initiate bidirectionally within a broad zone and proceed symmetrically, becoming unidirectional when one fork encounters a barrier in the vicinity of the previously designated leading strand origin (51-53).…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted "orthodox" hypothesis explaining the mode of mtDNA replication is the so called strand displacement model (Robberson et al, 1972;Goddard and Wolstenholme, 1980;Clayton, 1982). We can give here only a brief outline and refer to the reviews by Shadel and Clayton (1997) and Taanman (1999) for much more detailed description of the replication process.…”
Section: Model(s) Of Replicationmentioning
confidence: 99%